Improved Learning Outcomes of Sociology Subject of Social Interaction (Advertising) in Class X Students of State Senior High School 3 Sungguminasa Gowa - Sulvahrul Amin; Maria Ulviani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
The main problem in this research is how to improve the results of the sociology learning subject of social interaction (advertising) through a type of Jigsaw cooperative learning model in class X students at State Senior High School 3 Sungguminasa Gowa. This study aimed to improve the results of the sociology learning subject of social interaction (advertising) in class X students at State Senior High School 3 Sungguminasa Gowa. This type of research was a classroom action research consists of two cycles that conducted four times. Research procedures include planning, implementing actions, observing, and reflecting. The results showed that in the first cycle that was done, it has not been fulfilled because the average value obtained is 65.78. Whereas in the second cycle, from 27 students, there were 24 students or 88.89 had met the KKM and had been fulfilled the average value is 78.9 or in the high category, while the KKM standard was 70. Based on the findings of the research above it can be concluded the learning outcomes of class X sociology students at State Senior High School 3 Sungguminasa Gowa increased.